Growth Factor Receptor-Bound Protein 2 Contributes to ( Hem) Immunoreceptor Tyrosine-Based Activation Motif-Mediated Signaling in Platelets - Duetting, Sebastian; Voegtle, Timo; Morowski, Martina; Schiessl, Sarah; Schaefer, Carmen M.; Watson, Stephanie K.; Hughes, Craig E.; Ackermann, Jochen; Radtke, Daniel; Hermanns, Heike M.; Watson, Steve P.; Nitschke, Lars; et al. (Circulation Research, 2014)
Conclusions: These results reveal an important contribution of Grb2 in (hem)immunoreceptor tyrosine-based activation motif signaling in platelets in hemostasis and thrombosis by stabilizing the LAT signalosome.
Keywords: blood platelets; hemostasis; mice; signal transduction; thrombosis